A novel approach for flood hazard assessment using hybridized ensemble models and feature selection algorithms - Habibi, Alireza; Delavar, Mahmoud Reza; Nazari, Borzoo; Pirasteh, Saeid; Sadeghian, Mohammad Sadegh (International journal of applied earth observation and geoinformation, 2023)
Identifying flood-prone regions is critical for effective management of flood hazards as floods are among the most devastating natural disasters globally. However, accurate modeling and prediction of floods are challenging due to their complexity. The current research has proposed a novel approach for Flood Hazard (FH) prediction using hybrid Machine Learning (ML) models that integrate ensemble ML models with several Feature Selection (FS) algorithms. An optimum set of Flood Influential Factors (FIFs) was determined using the Simulated Annealing (SA) and Information Gain (IG) FS algorithms. The ensemble ML models employed include AdaboostM1 (ABM), Boosted Generalized Linear Model (BGLM), and Stochastic Gradient Boosting (SGB) algorithms. In addition, the hyper-parameters of the hybrid models were optimized using the random search (RS) method and repeated cross-validation technique. The proposed hybrid models were trained using flood inventory map and FIFs obtained from a spatial database. The results verified that the SA and IG algorithms detect 9 and 13 factors as FIFs in the FH assessment, respectively. Moreover, rainfall, distance to river, altitude, and lithology FIFs have a greater impact than the other factors in the Sardabroud watershed, Mazandaran Province, Iran. Several robust indicators, such as the area under curve (AUC) in relative operating characteristic (ROC) curves and statistical measurements, were employed to assess the robustness of hybrid models. SA-ABM model had the highest AUC value (0.983), while IG-ABM, SA-BGLM, SA-SGB, IG-BGLM, and IG-SGB had lower values (0.952 to 0.973). Finally, the SA-ABM hybrid model classified 27% of the study area as having a high hazard of floods.